Creep of Concrete Using Different Cement Types and Superplasticizer for Concrete Dams (International Journal of Engineering and Computer Science, 2017)
In mass concrete, creep itself may be a cause of cracking when the restrained concrete undergoes a cycle of temperature change due to the development of the heat of hydration and subsequent cooling. Few studies related directly to this matter which based on long-term experimental results. The effects of cement types and superplasticizer on creep of concrete revealed wide variations so that few generalizations could be made. In the current study three types of cement were used; Ordinary Portland cement (O.P.C.), Sulphate resisting cement (S.R.C.), and Blast-Furnace slag cement (S.C.). Superplasticizer was added by ratio 1% of weight of cement. The experimental results showed that the use of O.P.C. reduces creep by 33%- 37% compared with S.R.C. and S.C. concrete mixes. The use of 1% superplasticizer reduces creep by 28%- 34% compared with mixes without admixture. So, it is recommended to use O.P.C with 1% superplastisizer in concrete dams.